El Niño southern oscillation and seasonal drought drive riparian input dynamics in a Mediterranean stream. (28th October 2015) - Sanpera‐Calbet, Isis; Acuña, Vicenç; Butturini, Andrea; Marcé, Rafael; Muñoz, Isabel
Abstract: Inland waters substantially contribute to global carbon fluxes, and within them, low‐order forested streams are important processors of allochthonous organic matter (OM) inputs. Leaf litter quantity and quality are expected to change in response to global change (e.g., climate change, land use change) but few long‐term studies exist to better understand these shifts. The goal of this study was to assess the quantity and quality of OM sources to determine which global and local environmental factors control the dynamics of OM at the reach scale. The study was performed on a Mediterranean stream edged by a deciduous riparian forest over a 10‐yr‐time period. Riparian inputs, benthic and transported OM, and its carbon and nitrogen content were determined. The quantity of riparian inputs (912 ± 56 g dry mass m −2 yr −1 ) was comparable to temperate regions with deciduous riparian forests, but the Mediterranean climate determined the different dynamics of these inputs. El Niño Southern Oscillation was strongly related to the interannual variability in riparian inputs through changes in precipitation. The annual amount of inputs depended on previous cumulated nonflow periods, with successive nonflow periods causing a progressive decrease in riparian inputs. The distribution of inputs throughout the year followed either a unimodal or bimodal pattern according to the absence or presence of a nonflow period in summer. In addition, drought caused lower quality (higher carbon : nitrogen molar ratio) riparian inputs. Changes in the quantity and quality of OM were explained by both present and past local and global factors.